Gender and Inclusion Toolbox live launch - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 15 October, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), World Agroforestry Center (ICRAF) and CARE International coorganised a live-launch of a gender and inclusion toolbox in Nairobi, Kenya. The event included speakers from all three partners as well as the Food and Agriculture Organization of the United Nations (FAO). Presentations can be found on CCAFS Slideshare.